3D modelling of electrical capacitance and ultrasonic sensor integration using finite element method - Pusppanathan, Jaysuman; Abdul Rahim, Ruzairi; Phang, Fatin Aliah; Abas, Khairul Hamimah; Sahlan, Shafishuhaza; Mohamad, Elmy Johana (Penerbit UTM Press, 2015)
This paper presents a three dimensional (3D) modelling of a dual modality sensor composite which emerges electrical capacitance sensor (ES) and ultrasonic transducer (UT) for process tomography applications. The dual-modality tomography (DMT) setup has employed a customized ES electrodes along with UT on a single-plane. A finite element method is used to analyze the feasibility and the behavior of the DMT setup in 3D environment using COMSOL Multiphysics software. This simulation is performed both in a homogeneous and inhomogeneous conditions to investigate the wave distribution and its pattern thus the simulation results are presented in this paper.